Management of arsenic-laden water plant sludge by stabilization - Banerjee G.; Chakraborty R. (My University, 2025)
When arsenic is co-precipitated with iron hydroxide in an arsenic-removal water plant, a large quantity of sludge is generated which contains a good amount (an average of 6.1 kg As/m3 of sludge) of arsenic. The present paper attempts to find some suitable solutions to disposal of this arsenic-bearing sludge. As a safe means of disposal, stabilization processes such as briquette production, cement mortar and concrete making have been attempted in the present investigation. It has been found that in the preparation of briquette, cement-sand mortar and concrete, mixing up to 10, 18 and 40% of arsenic-bearing sludge by volume, respectively with the other common ingredients did not produce a TCLP leachate beyond its permissible direct inland water discharge standards of 0.2 g/m3 as stipulated by the Ministry of Environment & Forest, Government of India. Also, it was noted that 25% (by volume) of cement could be replaced by fly ash to stabilize arsenic-laden sludge to the tune of 11% by volume of cement-sand (1 : 3) mortar. © Springer-Verlag 2005.